Performing Faithfully Mechanisms of Fidelity in Oral Bible Translation - Ruge-Jones, Philip 1962- (2025)
The experience of a paperless, performance-based translation in a project of the Guatemalan Bible Society is explained. The end goal of this project is to provide memorized performances of biblical translations to local communities. This study examines quality assurance strategies which ensure that the final oral renderings and performances are faithful to both the biblical text and the cultural contexts of the people who will hear the passages.
Keywords: contextually faithful; textually faithful; Storytelling; oral Bible translation